PENENTUAN ION CU(II) SECARA FLOW-INJECTION ANALYSIS (FIA) SIKLIK DENGAN SENYAWA PENGKOMPLEKS 4-(2 PYRIDYLAZO) RESORCINAL (PAR)DAN ETILEN DIAMIN TETRA ASETAT (EDTA) - Norman Nurhakim, Muhammad
Spectrophotometrically, Copper(II) can be determined with 4-(2-pyridylazo)resorcinol (PAR) in the presence of EDTA. The absorption based on complexation copper(II) with PAR (red complex) which detectable by spectrophotometer and the obtained signals corresponded to copper(II) concentration. Cyclic FIA is based on the stability constant of copper(II)-EDTA complex (log K=18,8) which have bigger value than stability constant of copper(II)-PAR complex (log K=14,8). Therefore, copper(II)-PAR complex that through the FIA cell will go back to reservoir and ligand exchange occurred between copper(II)-PAR became copper(II)-EDTA, consequently the free PAR ligand will be regenerated and could be reused as ligand in the next determination of copper(II) ion. The aim of this experiment is to develop cyclic FIA system that can be used repeatedly in the determination of copper(II) ion. So, with this cylic FIA system will minimize reagents consumption, operating cost, and time.